Busana Jawa kuna - Noerhadi, Inda Citraninda, 1958- (Depok : Komunitas Bambu, 2012)
Classical Javanese clothing as sculptured in relief of Borobudur temple.
Includes bibliographical references (p. 107-112) and index.
Keywords: Borobudur (Temple : Magelang, Indonesia); Clothing and dress -- Indonesia -- Jawa Tengah